Endophytic Bacteria; Diversity, Characterization and Role in Agriculture - Abo-Koura, Hanaa A. (Journal of Basic & Applied Sciences, 2023)
Entophytic bacteria have an important role in the growth process and health of the plant host. Nevertheless, also some endophytic bacteria are existing in seeds and have not been studied yet. In addition, some Entophytic bacteria are important in plant tolerance to environmental stresses. They can colonize the internal tissues of the host and are able to use a variety of different relations including symbiotic, mutualism, communalistic, and trophobiotic. They have the ability for plant hormone production like auxin, indole acetic acid, and gibberellin; also some endophytic bacteria have the ability for siderophore creation, phosphate solubilization, nitrogen fixation, protease, and hydrogen cyanide formation.. Moreover, they produce compounds that could have possible usage in drug, agriculture or engineering. They have the ability to removesoil toxins thus, improving phytoremediation and soil fertility. Further, most of endophytic bacteria are diazotrophs and associated with the Proteobacteria, and a varied range has been detected agreeing to the nifH gene which codes for nitrogenase enzyme, structures recovered from plant materials, however a limited part of these genes looks to be stated. The endophytes discussed in this review are isolated from surface-disinfested plant tissue, and that do not damage the plant. Moreover, endophytes appear to be in-between saprophytic bacteria and plant pathogens, they are either saprophytes growing to be pathogens, or extremely grown plant pathogens with protective accommodation and nutrient provisions, but not killing their host. Generally, endophytic bacteria are partial under biotic and abiotic influences, with the plant itself being one of the main prompting influences.